Pelatihan Caregiver Lansia tentang Pertolongan Pertama pada Kondisi Mimisan, Tersedak dan Muntah pada Lansia - Monika Luhung; Emy Sutiyarsih; Eli Lea Widhia Purwandhani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction : Community partnership program activity with the title "Elderly Caregiver Training About First Aid for Nosebleeds, Choking and Vomiting in the Elderly at LKS-LU PL" is an activity intended for elderly caregivers who are responsible for the health of the elderly at LKS-LU PL”. Objective : The purpose of this community partnership program activity is to increase the understanding of knowledge and skills of caregiver at LKS-LU PL so that in caring for the elderly they can provide optimal first aid measures, especially in conditions of nosebleeds, choking and vomiting in the elderly. Method : The methods used in this training activity are lectures, discussions, and demonstrations on how to provide first aid for nosebleeds, choking and vomiting in the elderly. The result of the training from the red demonstration activity is that caregivers are able to correctly practice first aid for nosebleeds, choking and vomiting in the elderly. Result : The results of the second evaluation are from the participants' pre-test and post-test scores, the results show that 7 caregivers (50.00%) have good knowledge and 6 caregivers have sufficient knowledge (42.86%), a small proportion of 1 person (7.14%) has less knowledge. Meanwhile, the results of the post-test showed that all 14 caregivers (100%) had very good knowledge. Conclusion : It can be concluded that there is an increase in caregiver knowledge between before and after being given training. It is hoped that caregivers will be able to apply the knowledge and skills they have acquired during the training.